Power relations in Padre Cícero's epistolary political discourse: an investigation in the light of systhemic-functional grammar and critical discourse analysis - Souza, Vilmar Ferreira de (2011)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-graduação em Letras/Inglês e Literatura Correspondente